SDF-2 Induction of Terminal Differentiation in Dictyostelium discoideum Is Mediated by the Membrane-Spanning Sensor Kinase DhkA - Wang, Nancy (American Society for Microbiology, 1999)
SDF-2 is a peptide released by prestalk cells during culmination that stimulates prespore cells to encapsulate. Genetic evidence indicates that the response is dependent on the dhkA gene. This gene encodes a member of the histidine kinase family of genes that functions in two-component signal transduction pathways. The sequence of the N-terminal half of DhkA predicts two hydrophobic domains separated by a 310-amino-acid loop that could bind a ligand. By inserting MYC(6) epitopes into DhkA, we were able to show that the loop is extracellular while the catalytic domain is cytoplasmic. Cells expressing the MYC epitope in the extracellular domain of DhkA were found to respond only if induced with 100-fold-higher levels of SDF-2 than required to induce dhkA(+) cells; however, they could be induced to sporulate by addition of antibodies specific to the MYC epitope. To examine the enzymatic activity of DhkA, we purified the catalytic domain following expression in bacteria and observed incorporation of labelled phosphate from ATP consistent with histidine autophosphorylation. Site-directed mutagenesis of histidine(1395) to glutamine in the catalytic domain blocked autophosphorylation. Furthermore, genetic analyses showed that histidine(1395) and the relay aspartate(2075) of DhkA are both critical to its function but that another histidine kinase, DhkB, can partially compensate for the lack of DhkA activity. Sporulation is drastically reduced in double mutants lacking both DhkA and DhkB. Suppressor studies indicate that the cyclic AMP (cAMP) phosphodiesterase RegA and the cAMP-dependent protein kinase PKA act downstream of DhkA.